Model-Based Control Engineering Recent Design and Implementations for Varied Applications - Zakir Abdul Hamid, Umar; `Athif Mohd Faudzi, Ahmad (IntechOpen, 2022)
Progress in industrialization and automation engineering is creating many new opportunities in the autonomous systems industry. With the uncertain and highly nonlinear dynamics of the real world where these new technologies will be deployed, a reliable control strategy is necessary. This book provides a high-level discussion on model-based control engineering and its various applications.